HYPOLIPIDEMIC EFFECT OF ARGLABIN IN HEPATOMA TISSUE CULTURE - A. V. Ratkin; Yu. A. Pfarger; V. V. Ivanov; S. M. Adekenov; O. A. Kaidash; V. S. Chuchalin; V. V. Novitsky (Бюллетень сибирской медицины)
Objective. Investigation of hypolipidemic effect of sesquiterpene γ-lactone Arglabin in hepatoma tissue culture (HTC).Materials and methods. In this study we’ve evaluated the effect of sesquiterpene γ-lactone Arglabin and gemfibrozil (reference drug) on the lipid content in the hepatoma tissue culture (HTC) which were incubated with a fat emulsion “Lipofundin” by fluorescent method with vital dye Nile Red. The cell viability was investigated using the MTT-test and staining by Trypan blue.Results. Cultivation of cell cultures of rat’s hepatoma cell line HTC with Arglabin and gemfibrozil in concentrations from 10 to 50 μmol and from 0.25 to 0.5 mmol, respectively, had no cytotoxic effect. HTC cell viability did not change compared with the corresponding rate in the control culture. Experimental hyperlipidemia in hepatoma culture was induced by the addition in the incubation medium of fat emulsion “Lipofundin” in a final concentration of 0.05 %. The fluorescence intensity of Nile Red in the cells was increased 4-fold (p < 0.05), which indicates a significant accumulation of lipids in the cytosol of cells. In these steady-state Arglabin and gemfibrozil at concentrations 75–100 μM and 0.25–1.0 mM, respectively, reduced the content of lipid in cells. Conclusion. In the model of hyperlipidemia induced by lipofundin, sesquiterpene γ-lactone Arglabin prevents the accumulation of lipids in the HTC cell line, as evidenced by a decrease in Nile Red fluorescence. However hypolipidemic effect of Arglabin is associated with cytotoxic effects, which is typical for anticancer drugs.